Government's Restructuring Pay Policy and Job Satisfaction: The Case of Teachers in the Ga West Municipal Assembly of Ghana - Joseph Ato Forson; Rosemary Afrakomah Opoku (International School for Social and Business Studies, 2014)
This paper examines the 'aftermath effect' of the new civil service pay policy on job satisfaction among the teachers in Ghana. The study found that income, personal growth, bonus and organizational type had both direct and indirect effects on job satisfaction. The two-way analysis, as well as the multivariate analysis of variance, indicated that gender, age group, and educational background also played a role in determining the level of satisfaction among the teachers. The high unemployment rate (11%) and the implementation of the Single Spine Salary Structure (SSSS) for the public sector in 2010 are also contributing factors to the retention of teachers.